THE ROLE OF ISLAMIC EDUCATION IN SHAPING A CHARACTER-BUILDING GENERATION - Muslem Muslem (STAI Nusantara Kota Banda Aceh, 2026)
Islamic education plays a strategic role in shaping a generation that is not only intellectually superior but also possesses strong character and noble ethics. This article aims to examine the contribution of Islamic education to character development through the internalisation of spiritual, moral and social values derived from the Qur’an and Hadith. This study employs a qualitative approach using a literature review of various relevant books and academic journals. The findings indicate that Islamic education is capable of shaping students’ personalities through the balanced integration of cognitive, affective, and psychomotor aspects. This process is achieved through the instilling of the value of tawhid, the cultivation of noble ethics, the exemplary conduct of teachers, and the application of these values in daily life. Furthermore, Islamic education also serves as a moral bulwark in facing the challenges of globalisation and technological developments that may influence the character of the younger generation. Thus, Islamic education makes a significant contribution to fostering a generation of integrity, responsibility, and the ability to navigate the changing times wisely.